The Universal Periodic Review: A Valuable New Procedure for the Right to Health? - Judith Bueno De Mesquita (Harvard FXB Center for Health and Human Rights, 2019)
The right to health has been cast in increasingly broad terms in international human rights law, not only as a right to health care but also as a right to an ever more broad range of underlying and social determinants of health. Utilizing an analytical framework grounded in this broad view of the right to health, this article presents the findings of an empirical review of the right to health in the recommendations issued to states during the first two cycles of the Human Rights Council's Universal Periodic Review. The Universal Periodic Review, a peer-review mechanism, has come to occupy a prominent position in global human rights oversight, not least because all United Nations member states are regularly scrutinized under the procedure. It has also been identified as a potentially valuable mechanism to enhance accountability around the Sustainable Development Goals. The article highlights that the right to health is prominent in the Universal Periodic Review's recommendations, a conclusion that contrasts with existing perceptions that the right has been given limited attention by the procedure. However, the article argues that the quality of these recommendations is uneven. Increasing the engagement of key health stakeholders in the procedure will be important to enhance its potential for the right to health.